Feeding value of wheat and sorghum grain as indicated by absorbed nutrients - K.L. Gross; D.L. Harmon; T.B. Avery (Kansas Agricultural Experiment Station Research Reports, 1987)
Steers fed diets based on dry-rolled wheat or sorghum grain alone or combined (50:50) showed no differences in net portal fluxes of glucose, L-lactate, ammonia, urea, or α-amino nitrogen. Portal blood flow was increased in steers fed the 50:50 diet. Total volatile fatty acid flux into the portal blood tended to be lower for steers fed the sorghum grain diet, which may partially explain the lower feeding value of sorghum grain compared to wheat or the two grains combined.
Keywords: Cattlemen& #x27; s Day; 1987; Kansas Agricultural Experiment Station contribution; no. 87-309-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 514; Beef; Wheat; Sorghum grain; Nutrients